A comparative study on anti-MOG and anti-AQP4 associated optic neuritis following mild COVID-19: insights from a Chinese single-center experience - Sun, Liang; Wang, Jiawei; Yang, Qinglin; Guo, Yanjun (Frontiers in Neurology, 2024)
Background Research on the relationship between mild COVID-19 and the subsequent development of isolated optic neuritis (ON) with antibodies specific to myelin oligodendrocyte glycoprotein (MOG-ON) and aquaporin 4 (AQP4-ON) is limited, particularly case–control studies that directly compare these conditions within the same affected population. Methods A retrospective analysis of initial MOG-ON and AQP4-ON cases during the COVID-19 peak and subsequent months. Patients were classified as possible COVID-19 related ON (PCRON) or non-COVID-19 related ON (NCRON). The study compared epidemiology, comorbidities, and clinical features between these groups. Results Patients with MOG-ON tended to develop ON symptoms closer in time to a mild COVID-19 infection compared to those with AQP4-ON (6.87 ± 6.25 weeks vs. 11.06 ± 5.84 weeks; p = 0.038), a significantly higher proportion of patients with MON-ON developing symptoms within 6 weeks after COVID-19 compared to those with AQP4-ON (15/23 [65.2%] vs. 5/17 [29.4%]; p = 0.025). Comparing MOG-ON and AQP4-ON patients, MOG-ON patients were more likely to have a recent infection before ON onset (73.1% vs. 30%; p = 0.007) and had better peak and post-treatment visual acuity (p = 0.01; p < 0.001). In contrast, AQP4-ON patients frequently showed comorbid connective tissue diseases (30.0% vs. 0%, p = 0.004) and antinuclear antibody abnormalities (40.0% vs. 7.7%, p = 0.012). Among MOG-ON patients, PCRON had increased rates of atherosclerotic vascular diseases (AVDs) (53.3% vs. 9.1%, p = 0.036), phospholipid antibody abnormalities (60.0% vs. 18.2%, p = 0.04), and bilateral visual impairment (66.7% vs. 9.1%, p = 0.005). Multivariate analysis pinpointed AVDs (OR = 15.21, p = 0.043) and bilateral involvement (OR = 25.15, p = 0.015) as independent factors related to COVID-19 associated MOG-ON, with both being good discriminators for PCRON (AUC = 0.879). No differences were found between the PCRON and NCRON groups in AQP4-ON patients. Conclusion Mild COVID-19 is more likely associated with MOG-ON than AQP4-ON. MOG-ON that develops within 6 weeks following a COVID-19 infection may be associated with the COVID-19 infection. AVDs may have a synergistic effect on MOG-ON in patients with COVID-19, which warrants further investigation. COVID-19 related MOG-ON often affects both eyes, and acute visual function damage can be severe, but generally has a good prognosis.